MRI Biomarker for Early Diagnosis of Autism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
In order to identify early risk markers for autism spectrum disorder (ASD), investigators at University of California Davis School of Medicine and Davis Children's Hospital conducted a longitudinal brain MRI study of infant siblings in conjunction with behavioral assessments leading to an outcome classification at 24 months or later (mean age 32.5 months).